Bios–Technė–Logos - Kačerauskas, Tomas (Problemos, 2008)
The article etymologically analyses the ancient concepts bios, techne, logos. Additionally these concepts are interpreted in the context of the existential phenomenology. For this purpose not only Heidegger giving a tone for the existential interpretation of the ancient concepts, but also Husserl, Gadamer, Levinas and Bachtin are used. Three theses are presented: 1) our body is reliant on spiritual environment, where it matures and gains spiritual functions, i.e. it is spiritualized, named and realised; 2) spiritual environment at the same time is technical, where techne is interpreted as an art of creation of interactive components of environment - the body and the spirit; 3) logos as a word and a name supposes the text, i.e. the book which is written by our life, and the context, i.e. an interaction of texts as the life stories. Bios, techne and logos are interpreted in analogical way, i.e. as the interactive components of existential creation, which include the different planes of relations between spiritual environment and life stories developing in it. Bios is related with bodyness during the existential creation: our life from the birth to the death is inseparable from the whole of time and space where are involved the phenomena. On the other hand this whole is inscribed into our spiritual environment. Logos reflects linguistic-scriptual environment as spiritual context. Techne is interpreted both as an art of existential whole's creation and as an art of it's inscribing into this context.